Oncology clinicians' feelings towards patients presented in supervision: a pre-post assessment using the feeling word checklist - Stiefel, Friedrich; Bourquin, Céline; Wild, Beate; Schellberg, Dieter; Michaud, Laurent (Psycho-oncology, 2024)
Objective Clinical supervision of oncology clinicians by psycho-oncologists is an important means of psychosocial competence transfer and support. Research on this essential liaison activity remains scarce. The aim of this study was to assess the impact of supervision on oncology clinicians' feelings towards patients presented in supervision. Methods Oncology clinicians' (n = 23) feelings towards patients presented in supervision were assessed with the Feeling Word Checklist (FWC). The FWC was filled in by supervisees prior and after their supervision sessions (n = 91), which were conducted by experienced supervisors (n = 6). Pre- post-modification of feelings was evaluated based on a selection of FWC items, which were beforehand considered as likely to change in a beneficial supervision. Items were evaluated on session level using t-tests for dependent groups. Composite scores were calculated for feelings expected to raise and feelings expected to decrease and analysed on the level of supervisees. Results Feelings related to threats, loss of orientation or hostility such as “anxious”, “overwhelmed”, “impotent”, “confused”, “angry”, “depreciated” and “guilty” decreased significantly after supervision, while feelings related to the resume of the relationship (“attentive”, “happy”), a better understanding of the patient (“empathic”), a regain of control (“confident”) and being “useful” significantly increased. Feeling “interested” and “calm” remained unchanged. Significant increase or decrease in the composite scores for supervisees confirmed these results. Conclusions This study demonstrates modification of feelings towards patients presented in supervision. This modification corresponds to the normative, formative, and especially restorative function (support of the clinician) of supervision.